Groundwater treatment based on bubble aerator, ferrolite, resin, reverse osmosis and UV rays - GOUTOMO, BIMO TRI; PURWOTO, SETYO (Journal of Soil and Water Conservation, 2023)
Well water in the city of Surabaya, Indonesia has been heavily polluted by seepage of septic tanks and heavy metals, so the quality does not meet the quality standards of clean water. The purpose of this study was to improve the quality of well water using Bubble Aerator treatment and a series of Bubble Aerators, Ferrolite, Anion Resin, Cation Resin, Reverse Osmosis and UV Light. In this study, the variables used were the Bubble Aerator contact time of 30, 45, and 60 minutes, and the thickness of the Ferrolite media was 40, 45, and 50 cm. The results showed that the use of a Bubble Aerator in groundwater treatment obtained the best Fe and Mn removal, respectively 0.994 mg/L (98.37%) and 1.361 mg/L (99.32%) with a contact time of 60 minutes, while Fecal Coliform was 285 CFU/100mL (57%) with a contact time of 45 minutes. Meanwhile, for the treatment pair of Bubble Aerator, Ferrolite, Anion Resin, Cation Resin, Reverse Osmosis, and UV Light, the best reduction was 1.01 mg/L (100%) for Fe and 395 CFU/100 mL for Fecal Coliform (79%). In the bubble aerator treatment for 45 minutes with a Ferrolite thickness of 50 cm, while the Mn removal was 1.37 mg/L (100%) in the bubble aerator treatment for 60 minutes with a Ferrolite thickness of 50 cm.